Pengaruh Kompres Daun Kubis Terhadap Pengurangan Rasa Nyeri Mastitis Pada Ibu Menyusui - Emi Yulita; Yadriati Maya Pesa; Santi Agustina; Erika Erika (Universitas Pahlawan Tuanku Tambusai, 2026)
Breastfeeding problems that often arise in breastfeeding mothers are breast engorgement and even inflammation (mastitis). One effort to prevent breast engorgement is breast care. The purpose of this study was to determine the effect of cabbage leaf compresses on reducing the intensity of mastitis pain in breastfeeding mothers at the Rosita Independent Midwife Practice in Pekanbaru City. This observational analytical study with a quantitative design was conducted from November 2024 to September 2025 at the Rosita Independent Midwife Practice in Pekanbaru. The results. Meanwhile, based on the Wilxocon Test, the results of the intensity of breast pain before the management of cabbage leaf compresses were most painful as many as 15 respondents (100%) and the intensity of breast pain after the management of cabbage leaf compresses was most painful as many as 13 respondents (86.7%) with a p value of 0.000 with a significant difference for the scale of breast pain intensity before and after being given cabbage compress intervention with a p value of 0.000. Based on the results of the statistical test, a value of 0.000 was obtained (p value <α 0.05) so Ha was accepted, meaning there was a difference before and after the cold cabbage leaf compress intervention on the intensity of pain felt by postpartum mothers with an average change to a scale of 1 (no pain)